Environmental Performance, Green Accounting, Carbon Performance, And Firm Value: Does Board Meeting Frequency Matter? - Fransiskus Junior Sipangkar; Amrie Firmansyah (Jurnal Riset Akuntansi Terpadu, 2026)
Growing investor attention to corporate sustainability has increased the importance of understanding how environmental practices influence firm value. This study examines the effects of environmental performance, green accounting, and carbon performance on firm value while investigating whether board meeting frequency moderates these relationships. The study uses panel data on 24 energy companies listed on the Indonesia Stock Exchange during 2021-2024, yielding 80 firm-year observations selected through purposive sampling. Panel data regression is employed using STATA 17. The findings indicate that environmental performance has no significant effect on firm value. In contrast, green accounting and carbon performance exhibit significant negative effects on firm value. Furthermore, board meeting frequency mitigates the negative effects of green accounting and carbon performance on firm value but does not moderate the relationship between environmental performance and firm value. These findings suggest that sustainability-related initiatives do not always receive favorable market responses in Indonesia's energy sector and that active board oversight can mitigate adverse market perceptions of environmental investments. This study contributes to the literature by demonstrating the role of board meeting frequency in shaping the relationship between sustainability practices and firm value in an emerging-market context.